2016
DOI: 10.1080/02670844.2016.1159818
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of Ti6Al4 V implants by heat, H2O2 and alkali treatments

Abstract: In the present research we have applied three types of surface modifications on Ti6Al4 V alloy including heat treatment, H 2 O 2 treatment and alkali treatment. Scanning electron microscope and thin-film X-ray diffractometry (TF-XRD) were used to analyse the surface structure and the formed phases on the surface modified specimens. In vitro bioactivity evaluations were carried out and the cytocompatibility assay was performed using the evaluation of viability and attachment of L-929 fibroblast cells. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Results of the SBF immersion test are in agreement with previous studies [26,33], which reported accelerated deposition of Ca and P rich precipitates on the TiO 2 layer. Since hydroxyapatite has a composition similar to that of bone, deposition of hydroxyapatite during SBF test is generally assumed as a primary indicator of a bioactive surface, which has high potential to lead a good bonding between the implant and the bone in vivo [34,35].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Results of the SBF immersion test are in agreement with previous studies [26,33], which reported accelerated deposition of Ca and P rich precipitates on the TiO 2 layer. Since hydroxyapatite has a composition similar to that of bone, deposition of hydroxyapatite during SBF test is generally assumed as a primary indicator of a bioactive surface, which has high potential to lead a good bonding between the implant and the bone in vivo [34,35].…”
Section: Resultssupporting
confidence: 91%
“…This could be attributed to weak interaction (interfacial bonding) between the apatite layer and the surface of CoCr alloy. In the case of the oxidised sample, the apatite layer deposited on the TiO 2 layer was almost crackfree and stable (Figure3(b)), which indicates enhancement in the bioactivity of the CoCr alloy.Results of the SBF immersion test are in agreement with previous studies[26,33], which reported accelerated deposition of Ca and P rich precipitates on the TiO 2 layer. Since hydroxyapatite has a composition similar to that of bone, deposition of hydroxyapatite during SBF test is generally assumed as a primary indicator of a bioactive surface, which has high potential to lead a good bonding between the implant and the bone in vivo[34,35].…”
supporting
confidence: 91%
“…According to our recent researches, H 2 O 2 treatment is a corrosive phenomenon and reduces the mechanical properties of titanium scaffold [11]. We also showed that surface treatment of titanium alloy with H 2 O 2 solution for 30 min was not effective compared to the alkali treatment [12] and that H 2 O 2 treatment for 30 min did not significantly boost the bioactivity and cytocompatibility of titanium alloy. Karthega et al [13] reported that surface treatment of titanium with a 15wt% H 2 O 2 solution is more effective than 5wt% and 25wt% H 2 O 2 solutions for 1 h. Wen et al [14] used the H 2 O 2 solution to modify the surface of gradient structured titanium up to 48 h. According to our recent research [15], the surface of the H 2 O 2 treated titanium implant prior to heat treatment consists of amorphous titania, while after heat treatment at 600°C for 1 h, it is transformed into crystalline anatase which is a bioactive phase.…”
Section: Introductionmentioning
confidence: 84%
“…Micro/nano surface topography of implant surface directly influences the human cell adhesions after implantation. Surface modification alters the chemical composition, surface topography, and area surface roughness which directly impact surface properties concerning biocompatibility [2,3]. The literature illustrates that the hydrophilic surfaces with higher surface free energy promotes human tissue adhesion, protein adsorption, and osseointegration rate [4].…”
Section: Introductionmentioning
confidence: 99%